Gender Differences in Nutritional Status of Children in Tea Gardens of Darjeeling: Based on Conventional Indices and Composite Index of Anthropometric Failure - Subba, Dipika (International Journal of Child Health and Nutrition, 2021)
Objectives: The study aims to assess the nutritional status of children aged 1-5 years and its relationship with gender. Further, it also tries to assess the nutritional status of children using conventional indices and the composite index of anthropometric failure (CIAF) and suggests the appropriate method to estimate undernutrition among children. Materials and Methods: The area selected for the study is the tea gardens of Darjeeling. The study is based on the primary survey, and a total of 400 children were included in the study. A Chi-square test is conducted to find out the differences in the nutritional status of children gender-wise. Results: The analysis indicated that the level of undernutrition in tea gardens of Darjeeling is very high (51%). The level of undernutrition estimated through conventional indices indicated that the level of stunting, wasting, and underweight are 43.8%, 20.2%, and 36.2%, respectively, whereas the composite index of anthropometric failure estimated more prevalence rate (51.2%). The analysis indicates that the conventional indices underestimate the prevalence of undernutrition. On the contrary, a composite index of anthropometric failure (CIAF) gives better estimates of undernutrition. Both the indices of nutrition in the study area indicated higher undernutrition among girl children than a boy. However, no significant differences in the nutritional status gender-wise exist. Conclusion: The result depicts the positive sign as it contradicts the general belief that a boy child is more nourished than a girl. However, half of the children in tea gardens of Darjeeling aged 1-5 years, irrespective of gender, are undernourished. The paper highlights the urgent need to work out nutritional strategies to improve child health in the study area.